Targeting differential energy substrate metabolism on a therapeutic ketogenic diet: a case report - Russell, Kasey J.; Schwartz, Sarah E. O. (Frontiers in Nutrition, 2025)
Ketogenic diets show promise in treating a range of serious illnesses, yet their clinical utility is often hindered by poor adherence and difficulty achieving targeted ketone levels. Recommendations for patients pursuing ketogenic diets provide detailed dietary guidance but largely neglect the potential role of exercise on ketone levels. In a case study of a glioblastoma patient following a ketogenic diet, we present data suggesting that intensity of exercise may predict ketone levels above and beyond energy expended through exercise, and we propose a possible mechanism for this observed association. It is our hope that this case study will highlight the need for further research investigating how intense exercise in particular may influence ketone levels for patients on therapeutic ketogenic diets, potentially enabling patients to achieve higher ketone levels or allowing ketosis on more liberal diets.